CURRICULUM DEVELOPMENT FOR TEACHER TRAINING INSTITUTION (LPTK) IN MATCH WITH INDONESIAN QUALIFICATION FRAMEWORK (IQF) - Herlinawati, Herlinawati (Jurnal Bahasa Lingua Scientia, 2014)
Besides the Law number 12/2012 article 1, the higher education curriculum for study program is also mentioned in  Presidential Decree No. 8/2012 about  Indonesian Qualification Framework (IQF) and Permendikbud Number 73/2013.  It brings some impacts on several areas of education system, including curriculum in higher education, standard of workers’ competences and also the wage system. For LPTK, the level 6 of IQF which describes the generic competences  in detail as learning outcome (LO) can be a guide for the institution in redeveloping curriculum. Clearly mentioned that study program must design, implement and evaluate the curriculum based on IQF. The problem is IQF is still oriented mostly on recognition of qualifications meanwhile the requirements in designing academic oriented curriculum is still referred to Kepmendikbud No. 232 Tahun 2000 dan No. 045 Tahun 2002. therefore, implementing IQF in redeveloping curriculum for teachers education programs needs time to adapt curricula towards learning outcomes.